Dietary recommendations during the Covid-19 pandemic. Statement of the Committee of Human Nutrition Science of the Polish Academy of Sciences. - Lidia Wądołowska; Małgorzata Drywień; Jadwiga Hamułka; Piotr Socha; Maria Borawska; Mariola Friedrich; Ewa Lange; and other Members of the Human Nutrition Science Committee of the Polish Academy of Sciences (National Institute of Public Health - National Institute of Hygiene, 2021)
During the COVID-19 pandemic, care for an adequate diet, well adapted to the body's needs and the current level of physical activity, becomes of particular importance. Many dietary compounds participate in the functioning of the immune system, while vitamins D, C, A (including beta-carotene), E, B6, B12, folic acid, zinc, copper, selenium, iron, amino acids, n-3 and n-6 polyunsaturated fatty acids and intestinal microbiota are crucial in various types of defence processes. There has been no evidence that consumed food and its compounds, including those with pro-/prebiotic properties, play a significant role in preventing SARS-CoV-2 infection or alleviating its course. However, in terms of the nutritional value of food and the prevention of dysbiosis, recommending a varied diet with a high proportion of plant-based foods and an adequate amount of animal-based foods has a sound scientific basis. Malnutrition, underweight and obesity are considered independent and prognostic risk factors of severe SARS-CoV-2 infection, which reduce a patient's chances of survival. Therefore, ensuring good nutritional status, including healthy body weight, is a reasonable approach in the prevention of viral infection SARS-CoV-2 or alleviating its course. The document is accompanied by two catalogues of practical nutritional recommendations during the COVID-19 pandemic, addressed to the general population and children.